Toxicity of Soursop (Annona Muricata L) Leaf Extract and Patchouli (Pogostemon Cablin Benth) Leaf Extract to American Cockroach (Periplaneta Americana) - Ryhan Sasdar; Syamsiah; Andi Mu'nisa (Jurusan Biologi Universitas Negeri Makassar, 2023)
This study aims to determine the toxicity of soursop leaf extract (Annona muricata L) and patchouli leaf extract (Pogostemon cablin Benth) on the mortality of the American cockroach (Periplaneta americana). The extract was prepared using the maceration method, using distilled water as a solvent. Soursop and patchouli leaf extracts with a concentration of 5% were sprayed as much as 2 ml on each American cockroach. The results of the study were cockroach mortality data for 1-120 hours with observations every 1, 3, 6, 12 and 24 hours. As for the results obtained, the administration of soursop leaf extract cockroach mortality at the 24th hour was 66.67% and at the 48th hour 100% cockroach mortality. Whereas in the administration of patchouli leaf extract cockroach mortality at the 96th hour was 66.67% and at the 120th hour 100% cockroach mortality. These findings hold promising prospects for future research and applications. They suggest the potential development of natural cockroach control methods, the investigation of underlying mechanisms, and the evaluation of ecological implications and safety for human use. Additionally, these extracts may have commercial applications as pest control agents or insect repellents, offering more sustainable alternatives to conventional pest control methods.